Hubungan Tingkat Kecemasan dengan Kualitas Tidur pada Ibu Hamil Trimester III di Puskesmas Bago - Hoiriah, Maulidatul; Kurniawati, Dini; Juliningrum, Peni Perdani (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Pregnancy is the fertilization of the ovum and spermatozoa, followed by the nidation (implantation) process, which is classified into three trimesters. Mothers will experience increased anxiety when entering the third trimester, approaching delivery time. Anxiety has an impact, including feeling depressed and feeling uncomfortable, causing a decrease in sleep quality. The design used is descriptive correlation by measuring two variables, and the approach used is cross-sectional. Namely, the independent and dependent variables are carried out simultaneously. The population of this study were all pregnant women in their third trimester at the Bago Health Center. There were 84 populations, and the results of the sample calculation using the Lemeshow formula obtained 42 respondents. The sampling technique includes non-probability sampling. This study's results indicate a relationship between anxiety levels and sleep quality in third-trimester pregnant women at the Bago Health Center. The results of this study also show that anxiety levels have a strong relationship with sleep quality. The direction of the correlation in this study is negative, which means that if the level of anxiety is high, the quality of sleep is poor.